Promoting Teacher Professionalism through Character Building and Technology Integration - Fransisca Dwi Harjanti; Roely Ardiansyah (Jurnal Pendidikan Progresif, 2024)
Promoting Teacher Professionalism through Character Building and Technology Integration. Purpose: The purpose of this research is to identify the role of character education and technology incorporation at Teacher Education and Training Institutes in producing professional teachers as envisaged by the Teacher and Lecturer Law. Method: The type of research used in this study is the literature review. This entails gathering data from journals, research papers, government reports, and education policies. Findings: This study discovered that character education at Teacher Education and Training Institutes assists in the formation of professional teachers through the acquisition of appropriate attitudes and values. Some of these are relationships with self, the law, professional associations, students, peers, and supervisors. Some of the values include faith, openness, honesty, lifelong learning, enthusiasm, unity, togetherness, discipline, and responsibility that are useful for future teachers. Including the technology integration in the training assists in enhancing these professional values and skills. Conclusion: The programs of character education and integrating information and communication technology at Teacher Education and Training Institutes are useful in producing professional teachers with content and character. This assists in producing teachers who are able to impart positive values in the learners such as love for God, parents, fellow human beings, and country. Keywords: character building, professionalism, demoralization.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202463